Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ Approach of Curamericas: 7. The empowering effect of Care Groups - Corey Gregg; Mario Valdez; Ira Stollak; Shayanne Martin; William T. Story; Henry B. Perry (BMC, 2023)
Abstract Background While there is extensive published evidence regarding the effectiveness of the Care Group Approach in promoting community-wide health behavior change, there is no published evidence regarding its empowering effect on its participants. Our study aimed to understand if the Care Group Approach as applied in the Curamericas/Guatemala Maternal and Child Health Project in isolated rural mountainous communities in Guatemala produced evidence of empowerment among the female participants. This is the seventh of 10 papers describing the expanded Census-Based, Impact-Oriented (CBIO+) Approach in improving the health and well-being of mothers and children in the rural highlands of the Department of Huehuetenango, Guatemala. Methods We conducted semi-structured individual and group interviews with 96 female Care Group participants -including Level-1 Care Group Promoters, Care Group Volunteers, and Self-Help Group participants. The participants were from six communities - two from each of the three municipalities making up the Project Area. Data were analyzed both using deductive thematic and by exploring the following social constructs: perceived social status, self-efficacy, decision-making autonomy, and formation of social capital. Results The findings supported the hypothesis that Care Group participation was an empowering process. The primary themes that emerged included increased respect accorded to women in the community, women's willingness and ability to make decisions and their confidence in making those decisions, and the development of stronger bonds among Care Group members, with other community members, and with community leaders. Conclusion Through increased theoretical and practical knowledge about important maternal and child health matters and through the social experience of obtaining this knowledge and sharing it with other community members, participation in the Care Group Approach empowered participants to make positive health behavior changes for themselves and for their children and families. This, in turn, led many participants to become more engaged in community activities for improved health and beyond, thereby enhancing social capital in the community. We conclude that the Care Group Approach, as applied in this setting, has made it possible for marginalized indigenous women living in a male-dominated society to become more empowered.